The Impact of the Application of SQ3R Method (Survey, Question, Read, Recite, Review) Towards Students’ Reading Comprehension - Ni Nengah Parwati (International Conference on Education and Language (ICEL), 2014)
In learning English, students faced difficulty in comprehending text. The purpose of this quantitative research was to find out wether there is impact of the application of SQ3R method (Survey,Question, Read, Recite, Review) Towards Reading Comprehension of Senior High School Level. The students divided into two groups; one experimental group and one control group. The writer gave a pre-test and a post-test to the both groups. The pre-test was distributed before treatments, while the post-test after the treatments. The treatments were teaching of reading by using SQ3R method which was performed by the researcher. The data collected with the tests were statisficallyanalysed. T-test for two group design was applied. The result indicated that p-value 1%: 2.65 and 5%: 2.00 and t-test value is 20,95. Therefore, the alternative hypothesis (Ha) was accepted but the null hypothesis (Ho) is rejected. The writer concluded that SQ3R method (Survey, Question, Read, Recite, Review) gave a significant effect to the students’ reading comprehension.